HUBUNGAN AKUNTANSI PERTANGGUNGJAWABAN DENGAN EFEKTIFITAS PENGENDALIAN BIAYA (Studi Pada PMI Daerah Aceh) - Elviza - (Jurnal Akuntansi Muhammadiyah (JAM), 2012)
The purpose of this study was to determine the relationship of accounting to evaluate the effectiveness of cost control and accounting concepts are applied as a management tool in an organization to achieve effective cost control.               The collection of data and information that is needed in this research field research (field research), the data used are primary data, obtained directly from the subject of research in the form of respondent perceptions by circulating a list of questions about accounting in the form of questionnaires to 6 respondents the finance staff in each division at the Indonesian Red Cross in Aceh and analysis that reports the difference in the budget documents with the realization to know the effectiveness of cost control, processed and analyzed and compared with existing theory while testing the data necessary steps that test data and the design of hypothesis testing.             The results showed that, there is a positive relationship between the effectiveness of the accounting cost control, testing performed using Kendall rank correlation coefficient analysis of the results of 0.828 or 82%. Keywords : Responsibility Accounting, Cost Control Effectiveness